Concept Map: Does It Increase Learning Motivation of Student? - Aisyiyah Dinnur Utami; Eko Yuliyanto (Universitas Negeri Yogyakarta, 2020)
The learning model used by a teacher is a factor that supports the success of learning during the process of teaching and learning activities. The particular study aimed to determine differences in student learning outcomes and motivation before and after for learning using the concept map model in the material of chemical atomic structure for class X. This study used a quasi-experimental research method with the One Group Pretest-Posttest Design research design. The sample was 36 students from class X and selected using a purposive sampling technique. A test instrument was used to collect data of learning outcomes and a questionnaire used to collect data of student's motivation, and a pretest and posttest were carried out. Analysis of hypothesis test used Paired Sample T-Test. The results of this study were: (1) there were significant differences in term of student’s learning outcomes before and after learning treated using a concept map model in chemistry subject for the material of the atomic structure, and (2) there was a decreasing in term of student’s motivation before and after learning treated using concept map model in chemistry subject for the material of the atomic structure.